FOOD SECTOR ANALYSIS IN INDONESIA: A SOCIAL ACCOUNTING MATRIX (SAM) APPROACH - Muryani, Muryani (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
The development of the agricultural sector has a made great contribution to the change in the Indonesian economy. In the national policy, the government has prioritized the subsidies in the agricultural sector to stimulate it to be more productive. This research has some aims i.e.: to describe the role of the agricultural sector based on the distribution of household income groups in Indonesia; to describe the impact of household income level groups if the subsidies in the agricultural food sector or Indonesia have increased. The food sectors are classified into: sector production of: rice.corn and soybeans.other crops.poultry meat (traditional farms).poultry meat (medium and large farms),eggs,forestry and hunting,fishing and others. The results show that the food industry has experienced a significant increase in productivity among the economic sectors. Agricultural entrepreneurs are the group that experienced a high increase in income among farming households Keywords: sector, food,  policy, SAM,  revenue